Communication on Sciences Framework: an interview with Robert K. Logan - Braga, Adriana (E-Compós, 2011)
In this exclusive interview for E-Compós, Dr. Logan tells about his career, his collaboration with Marshall McLuhan, Communication Theory and interdisciplinary approaches to Communication Sciences.